2016
DOI: 10.1177/1475725716661872
|View full text |Cite
|
Sign up to set email alerts
|

Do Exam Wrappers Increase Metacognition and Performance? A Single Course Intervention

Abstract: Previous research has indicated that an intervention called ''exam wrappers'' can improve students' metacognition when they are using wrappers in more than one course per academic term. In this study, we tested if exam wrappers would improve students' metacognition and academic performance when used in only one course per academic term. A total of 86 students used either exam wrappers (an exercise with metacognitive instruction), sham wrappers (an exercise with no metacognitive instruction), or neither (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 18 publications
2
57
2
2
Order By: Relevance
“…To date, it appears that only one study has explored the use of exam wrappers in a psychology course scientifically. Sociher and Gurung (2017) explored metacognitive skills and exam wrappers in community college courses. In this study, the authors found that when using exam wrappers on the day, tests were returned and handing back the exam wrappers the next class period, no benefit was seen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, it appears that only one study has explored the use of exam wrappers in a psychology course scientifically. Sociher and Gurung (2017) explored metacognitive skills and exam wrappers in community college courses. In this study, the authors found that when using exam wrappers on the day, tests were returned and handing back the exam wrappers the next class period, no benefit was seen.…”
mentioning
confidence: 99%
“…Given the large number of reported successes with exam wrappers have shown in the literature (Soicher & Gurung, 2017; Stephenson et al, 2017, notwithstanding), I sought to explore whether exam wrappers would be useful in an undergraduate psychology course. Based on the extant literature, I expected that the exam wrapper would improve student performance.…”
mentioning
confidence: 99%
“…Regulation of cognition items include, for instance, "I try to translate new information into my own words," "I ask myself questions about the material before I begin," and "I summarize what I've learned after I finish." Although scoring options for the MAI vary from a bipolar sliding scale (Schraw & Dennison, 1994) to a 5-point Likert scale (Harrison & Vallin, 2018), we chose to use a dichotomous version as per Soicher and Gurung (2017). Students indicated whether the statement was "true or false as it generally applies to you when you are in the role of a learner."…”
Section: Implementation Of the Maimentioning
confidence: 99%
“…Such an exercise prompts students to think critically and constructively about their performance, guiding them to be more metacognitive and plan more successful approaches in the future. Results of research on the effects of using exam wrappers on students' course performance and/or metacognitive awareness are mixed (Kustritz & Clarkson, 2017;Lovett, 2013;Rosales et al, 2019;Soicher & Gurung, 2017;Trogden & Royal, 2019). Teaching metacognition to students can have a positive impact on their performance (Cook et al, 2013;Zhao et al, 2014).…”
mentioning
confidence: 99%
“…Wrappers are typically writing assignments that ask a student to reflect upon their thinking at the time they performed an assessment task such as an exam. Exam wrappers typically cause students to examine their study habits and approaches, identify aspects that are not proving beneficial and implement different approaches to study [29][30][31][32][33]. Wrappers can be applied to homework [34] and activities other than exams, and they can ask students to reflect upon aspects of their thinking other than the way they studied and prepared.…”
Section: Research Hypothesesmentioning
confidence: 99%